Perceptions of emotional abuse in the coach–athlete relationship in youth sport: The influence of competitive level and outcome. Issue 6 (December 2016) - Gervis, Misia; Rhind, Daniel; Luzar, Amber
Emotional abuse has been highlighted as a key issue within the youth sport context. The present study investigated how perceptions of emotional abuse are influenced by situational factors. Two hundred and eight participants (107 athletes and 101 coaches) were shown a series of vignettes depicting emotionally abusive behaviour by a coach towards a 14-year-old athlete. Differences in perceptions were explored in relation to the level of competition (elite, county and club) and performance outcome (successful/unsuccessful) depicted in the vignette. Participants rated each vignette on a 5-point scale in terms of the extent to which the coach's behaviour had an impact on the athlete's performance and well-being as well as the perceived commonality and acceptability of the behaviour. Two-way ANOVAs revealed that competitive level and performance outcome, both as main effects and as an interaction, significantly influenced perceptions. These findings can inform policy and practice to change attitudes and behaviours which support and justify emotionally abusive behaviours in youth sport contexts.